State of the Art of the Evaluation of Health Technologies in Latin America - Martínez-Licona F. M.; Ortiz-Posadas, M. R.; Ortiz-Pedroza, M. R. (Revista Mexicana de Ingenieria Biomedica, 2019)
The emergence and development of health technologies have intensified the role of their evaluation in recent years, causing a growing interest in the Evaluation of Health Technologies (ETES) in Latin America, through attempts to provide useful information to the decision-maker. This article presents a review of the state of the art of ETES in Latin America, from the analysis of publications in journals and specific events. Three aspects were addressed: eva-luation elements, methods that are applied, and resulting policies. The following evaluation aspects were found: safety, efficacy, effectiveness and efficiency, economic-financial, clinical and technical, the latter with more signifi-cant development. Concerning the methods, proposals for empirical strategies for the analysis of information and decision making were found. The generation of public policies related to the HTA in Latin America is under develo-pment, national problems are hardly being identified, and the strategies to be followed for their solution. Therefore, there is a need to continue working on the development of policies, and methods of HTA in the Latin American region that allow responding to the health problems of the population of each country.